2018
DOI: 10.1007/s00401-018-1937-5
|View full text |Cite
|
Sign up to set email alerts
|

TIA1 regulates the generation and response to toxic tau oligomers

Abstract: RNA binding proteins (RBPs) are strongly linked to the pathophysiology of motor neuron diseases. Recent studies show that RBPs, such as TIA1, also contribute to the pathophysiology of tauopathy. RBPs co-localize with tau pathology, and reduction of TIA1 protects against tau-mediated neurodegeneration. The mechanism through which TIA1 reduction protects against tauopathy, and whether TIA1 modulates the propagation of tau, are unknown. Previous studies indicate that the protective effect of TIA1 depletion correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 50 publications
7
87
2
Order By: Relevance
“…A growing body of evidence suggests that tau plays a causal role in mediating neurodegeneration and is strongly correlated with cognitive decline in AD and related diseases ( 62 , 63 ). Tauopathies comprise a large group of age-related neurodegenerative diseases, characterized by predominant accumulation and deposition of pathological tau aggregates or in combination with other toxic amyloid aggregates ( 18 , 23 , 50 , 64 67 ). Recent evidence has suggested that the accumulation of tau is mediated through the spreading of misfolded tau seeds from cell-to-cell and from initial brain regions throughout the brain in a trans-synaptic pattern as the disease progresses, thus proposing a prion-like mechanism for tau protein to propagate the disease ( 19 , 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that tau plays a causal role in mediating neurodegeneration and is strongly correlated with cognitive decline in AD and related diseases ( 62 , 63 ). Tauopathies comprise a large group of age-related neurodegenerative diseases, characterized by predominant accumulation and deposition of pathological tau aggregates or in combination with other toxic amyloid aggregates ( 18 , 23 , 50 , 64 67 ). Recent evidence has suggested that the accumulation of tau is mediated through the spreading of misfolded tau seeds from cell-to-cell and from initial brain regions throughout the brain in a trans-synaptic pattern as the disease progresses, thus proposing a prion-like mechanism for tau protein to propagate the disease ( 19 , 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Late-stage pathology also exists, which is made up of insoluble RBPs or tau molecules that appear to be consolidated into relatively homogeneous pathological aggregates, in which associated proteins become excluded 56 . Studies using seeding and propagation (described below) suggest that tau pathology evolves in a manner similar to TDP43 pathology, proceeding through a SG intermediate 134 .…”
Section: Stress Granules and Tau Aggregationmentioning
confidence: 99%
“…Other groups have shown that the propagated Tau oligomers lead to reduced long-term potentiation and increased short-term depression effect on cortical neurons, which has been partially blocked by the administration of oligomer-specific antibody [13,14]. Oligomers are the unstable species with neurotoxicity and inflammatory activity, which acts as a seed for further aggregation [13,15,16]. Mirbaha et al have evidenced that the small size and confirmation of Tau oligomers (mainly, trimer) are ideal for cellular uptake and propagation [17].…”
Section: Introductionmentioning
confidence: 99%